Sosialisasi Penentuan Guru Terbaik pada SMPN 17 Padang dengan Metode MOORA - Guswandi, Dodi; Hafizh, M.; Novita, Triana (LPPM Universitas Dharma Andalas, 2024)
The determination of the best or outstanding teachers in the school has not been done objectively or in other words, the selection of the best teachers is still carried out in a subjective way where validation in determining the openness is not known. So to overcome this problem, the author proposes to apply the calculation of the Decision Support System (DSS) in solving the problem. The method used in Community Service (PKM) is the MOORA method and uses the criteria weighting method with Centroid Rank Order. The design of this DSS system is implemented in applications using the JAVA programming language so that management can easily use it. Using this Decision Support System can make it easier for the Principal of SMPN 17 Padang to determine the best teacher with the aim of rewarding or appointing even better positions to the best teachers.